The Development of Immune System Smart-Flash Multimedia as Learning Media in MA - Rahayu, Sinta; Saptono, Sigit (Journal of Biology Education, 2021)
This study aimed to see the multimedia characteristics of the Smart-Flash Immune System that has been built, the validity of the content and readability, and to see the applicability of Immune System Smart-Flash multimedia. The research was conducted using the Research and Development (R&D) method with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) research model. The data taken in this study were the validity of the Immune System Smart-Flash multimedia in terms of material and media by experts, as well as the application of Immune System Smart-Flash multimedia data in the form of the results of filling out questionnaire responses by students and teachers. The results showed that the Immune System Smart-Flash multimedia had 4 factors, namely it can be used independently by students, has attractive features and display designs, has an animated video that is connected to the original website, and has an evaluation in the form of a puzzle game. The results of validation of material experts 1 and 2 and media experts 1 and 2 were 95%, 90%, 87%, and 87% respectively with very feasible criteria. The responses of students and teachers 1 and 2 obtained a proportion of ≥80% with the overall criteria being very good. Based on the research results, it can be seen that Immune System Smart-Flash multimedia was very suitable for use in learning activities.